A Character-Based Learning Model to Foster Independence in Early Childhood Islamic Education - Titi Chandrawati; Susy Puspitasari; Siti Aisyah; Siti Julaeha; Dian Novita; Muktia Pramitasari; Monika Handayani (GHAITSA : Islamic Education Journal, 2026)
This study examines the development and implementation of a character-based learning model designed to foster independence among early childhood learners in Islamic educational settings — specifically Raudhatul Athfal (RA) and PAUD Islam. Grounded in Islamic moral values of amanah (trustworthiness), mas'uliyyah (responsibility), and ta'awun (cooperation), the model integrates structured lesson plans, Islamic narrative big books, and character-themed nasyid (Islamic songs) into daily classroom practice. Employing a Research and Development (R&D) approach based on the Borg and Gall model (2007), the study was conducted with 10 early childhood educators and their students aged 4–6 years across institutions in Tangerang and Sawangan, Indonesia. Pre- and post-intervention data revealed a significant increase in children's independent behaviors from 37% to 83%, alongside substantial growth in teacher instructional competence and confidence in delivering character-integrated Islamic education. The model demonstrates strong scalability and cultural resonance within Indonesia's Islamic early childhood education system, contributing a pedagogically robust and spiritually grounded framework for character education aligned with national curriculum mandates and Islamic values